2021
DOI: 10.1038/s41467-021-27461-8
|View full text |Cite
|
Sign up to set email alerts
|

Istaroxime treatment ameliorates calcium dysregulation in a zebrafish model of phospholamban R14del cardiomyopathy

Abstract: The heterozygous Phospholamban p.Arg14del mutation is found in patients with dilated or arrhythmogenic cardiomyopathy. This mutation triggers cardiac contractile dysfunction and arrhythmogenesis by affecting intracellular Ca2+ dynamics. Little is known about the physiological processes preceding induced cardiomyopathy, which is characterized by sub-epicardial accumulation of fibrofatty tissue, and a specific drug treatment is currently lacking. Here, we address these issues using a knock-in Phospholamban p.Arg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 66 publications
3
21
0
Order By: Relevance
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…GO term analysis did not identify overrepresentation of any terms in either gene set (false discovery rate <0.05). However, among the downregulated transcripts, we found three well-characterized myocardial genes including phospholamban ( pln/plna ), 63 , 64 atrial myosin heavy chain 6 ( myh6 ), 65 and natriuretic peptide precursor a ([ nppa ] 66 , 67 ; Figure S8B ; Table S3 ). We documented trending downregulation of nppa by reverse-transcription quantitative PCR (RT-qPCR) at 33 hpf ( Figure S7C ).…”
Section: Resultsmentioning
confidence: 99%
“…In Zebrafish, the plna R14del variant causes beat-to-beat variations in cardiac output in the absence of cardiac remodeling, suggesting that the cardiac contractile dysfunction is not caused by but rather causal for cardiac remodeling. 36 Causal relationships between anomalies in the QRS complex, specifically in the Q-R upslope, and increased risk of DCM have been found through the Mendelian Randomization approach using genetic variants of ECG signatures 37 .…”
Section: Discussionmentioning
confidence: 99%